GAMBARAN SIKAP PENDIDIKAN KESEHATAN DENGAN ROLE PLAYING TENTANG PENCEGAHAN SEKS BEBAS PADA PADA MAHASISWA PRODI D III KEBIDANAN - Puspitaningrum, Dewi; Istiana, Siti (LPPM STIKES MUHAMMADIYAH GOMBONG, 2015)
Free sex is an exploration or try and as an outlet for fun. Based on the above phenomenon, we need a health education, which is expected to role-playing method of prevention can change the behavior of free sex free sex positive prevention, where the method of role playing is a way of mastering the learning materials through the development of students' imagination and appreciation. This study aims to describe the health education on the prevention of sexual role playing freely. The method used is descriptive number of 90 student population, with a sample of 47 female students with simple random sampling technique. The research data collection by using instruments such as questionnaires and role playing scenarios.The results of this study indicate the attitude of the respondent before health education with the support of role playing as many as 28 respondents (59.6%) and that do not support as many as 19 respondents (40.4%). And after health education with role playing obtained that supports as many as 34 respondents (72.3%) and that do not support as many as 13 people (27.7%). The results of this study has been no improvement after the method of role playing, so that the learning methods that lead on the prevention of free sex easier terstimulus expected positive behavior on the prevention of free sex. Suggestions of this study can stimulate positive behavior in the prevention of teen sex, emphasizing preventive health curriculum on sex, as well as improve the community involved in supporting the prevention of free sex attitudes regardless of it's taboo.Â Keywords: attitudes of health education, preventive free sex, role playing